Hospitalidad y singularidad - Mosto, Marisa (Sapientia, 2019)
The singularity and reciprocity are essential features of the hospitality relationship and are against the current spirit with its tendency to abstraction and the predominance of the quantitative. We put Christoph Theobald's thought in relation to Pavel Florenski's thinking on this topic and we try to reflect his ideas in the evangelical passage of hemorrhage (Mc 5, 21-34; Mt 9, 18-26; Lc 8, 40-56). A tradition of Christianity links the hemorrhoidal woman with the character of Veronica. Veronica would be one of those responsible for the transmission of the Holy Face, the source of Byzantine and Russian iconography. This tradition is testimony and symbol of the presence of the wisdom of singularity as an essential element also in the spirituality of iconography, making hospitality one of the keys to understanding the life of prayer.